THE SEPARATE SELECTIVE INDICES CHARACTERISTIC OF WHITE-HEADED UKRANIAN CATTLE - Шуплик, В. В.; Каспров, Р. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The article presented the investigation selective indices results of 226 white-headed Ukrainian cows of different age. The following parameters have been investigated: milk drawn amount at one milking, milk fattiness, milk fat amount in the period of lactation, lactation length, age of the first insemination and calving, duration between calving and service period, cow dropout causes from the basic herd. As the research has determined, milk drawn amount at one milking in a standard herd made 4560 kg under fattiness of 3,63%. The milk yield has been reduced after the second lactation. However the milk yield has been increased in the next lactations up to the sixth lactation. The cow reproduction assessment showed that the first effective insemination was fairly late (after 26 months) and the first calving - after 36 months. The amount of an inter-calving period made 396,8 days and a service period – 118,6 days, the reproduction coefficient made 0,92. 166 cows have dropped out from the herd in the analyzed period, among them: by low productivity reason - 140 cows (84,3%), by gynecological diseases reason - 8 (4,8%) and diseases of quarters - 6, 3,6%. The white-headed Ukrainian cows do not suffer from leucosis and tuberculosis.